Focal adhesions are essential to drive zebrafish heart valve morphogenesis - Gunawan, Felix (J Cell Biol, 2019)
Elucidating the morphogenetic events that shape vertebrate heart valves, complex structures that prevent retrograde blood flow, is critical to understanding valvular development and aberrations. Here, we used the zebrafish atrioventricular (AV) valve to investigate these events in real time and at single-cell resolution. We report the initial events of collective migration of AV endocardial cells (ECs) into the extracellular matrix (ECM), and their subsequent rearrangements to form the leaflets. We functionally characterize integrin-based focal adhesions (FAs), critical mediators of cell–ECM interactions, during valve morphogenesis. Using transgenes to block FA signaling specifically in AV ECs as well as loss-of-function approaches, we show that FA signaling mediated by Integrin α5β1 and Talin1 promotes AV EC migration and overall shaping of the valve leaflets. Altogether, our investigation reveals the critical processes driving cardiac valve morphogenesis in vivo and establishes the zebrafish AV valve as a vertebrate model to study FA-regulated tissue morphogenesis.